INFLUENCE OF SOCIAL SUPPORT, SELF-EFFICACY, AND FINANCIAL STRESS ON QUALITY OF LIFE OF RETIRED AND NON-RETIRED ELDERLY IN TIDORE KEPULAUAN CITY - Latuconsina, Nurgaip; Krisnatuti, Diah; Johan, Irni Rahmayani (Universitas Padjadjaran, 2024)
Elderly are frequently encountered with various problems such as low social support, self-efficacy, and financial stress, affecting quality of life. Therefore, this research aimed to analyze the influence of social support, self-efficacy, and financial stress on the quality of life of the elderly in Tidore Kepulauan. A cross-sectional research design was used, and data were obtained from interviews with 200 retired and non-retired elderly respondents. The data analysis also used descriptive and inference methods using the SPSS 25.0 program. The results showed that the majority of elderly retirees received high levels of social support, while 60% of non-retired elderly experienced low social support. This research further revealed that eight out of ten had moderate self-efficacy. Financial stress for all elderly was low because social and financial support was high. The quality of life of the retired elderly was better than that of their counterparts due to their high income. Elderly employment, years of education, and income positively correlated with quality of life, suggesting that higher education and income led to better quality of life. Additionally, the regression test results showed that social support had a significant positive effect, and financial stress had a substantial negative impact on the quality of life of retired and non-retired elderly. This implied that higher social support and lower financial stress led to higher quality of life for both groups. Lansia kerap diperhadapkan pada berbagai permasalahan seperti rendahnya dukungan sosial, self efficacy dan financial stress yang mempengaruhi kualitas hidupnya. Penelitian ini bertujuan untuk menganalisis pengaruh dukungan sosial, self efficacy, financial stress terhadap kualitas hidup lansia di Pulau Tidore. Penelitian ini menggunakan desain cross sectional study. Data dikumpulkan dari hasil wawancara kepada 200 responden lansia pensiunan dan non pensiunan. Analisis data meliputi analisis deskriptif dan inferensia menggunakan program SPSS 25.0. Hasil penelitian menunjukan bahwa dukungan sosial yang diperoleh oleh mayoritas lansia pensiunan terkategori tinggi. Sementara itu, enam dari sepuluh lansia non pensiunan memiliki dukungan sosial yang rendah. Delapan dari sepuluh lansia pensiunan dan lansia non pensiunan mempunyai self efficacy terkategori sedang. Financial stress seluruh lansia pensiunan dan non pensiunan terkategori rendah. Kualitas hidup lansia pensiunan lebih baik dari lansia non pensiunan. Pekerjaan, lama pendidikan dan pendapatan lansia berkorelasi positif signifikan dengan kualitas hidup lansia, artinya semakin baik tingkat pendidikan dan pendapatan lansia, semakin baik pula kualitas hidupnya. Hasil uji regresi menunjukan bahwa dukungan sosial positif signifikan dan financial stress negatif signifikan berpengaruh terhadap kualitas hidup lansia penisunan dan non pensiunan. Artinya semakin tinggi dukungan sosial dan semakin rendah financial stress akan semakin tinggi kualitas hidup lansia pensiunan dan non pensiunan.